Van Coller, H. 2020. Regulating religion: State governance of religious institutions in South Africa. Routledge: London. 246 pages. ISBN: 978-1-138- 29871-2 (hardback). - Idowu A Akinloye (Journal for the Study of Religion)
Prof Helena van Coller’s book is topical and timely relevant, given that South Africa is a multi-religious state, and more importantly because the intersection between law and religion has increasingly been a subject of controversy for some years in South Africa.